Evaluation of Pain Reduction and Clinical Efficacy of Feedback-Controlled Ultrasonic Scaler - Min-ju Kim; Hee-jung Lim; Myoung-hee Kim; Young-sun Hwang; Im-hee Jung (The Korean Society of Dental Hygiene Science, 2023)
Background: Recently, a piezoelectric ultrasonic scaler based on a feedback control mechanism was introduced for pain relief. This study aimed to investigate the effects of a new ultrasonic scaler in reducing pain and discomfort in adults. Methods: A newly introduced ultrasonic scaler (Master 700Ⓡ) was used as the test device and a conventional ultrasonic scaler device (PIEZONⓇ) was used as the control device. Forty-one healthy adults visited the dental clinic for dental scaling but did not undergo scaling or periodontal treatment within 6 months. Intraoral examinations were performed before scaling and 3 months later; before scaling, both devices were randomly assigned on the left or right side of each dentition (split-mouth model) and scaling was performed by a registered dental hygienist. The levels of pain and discomfort during scaling were evaluated subjectively and objectively using the visual analog scale (VAS) and physiological monitoring of the heart rate (HR), respectively. Time was measured for each device. Results: All clinical indicators, except bleeding on probing, significantly improved with both devices. The treatment times were 7 minutes, 13 minutes (control) and 6 minutes, 59 minutes (test). VAS scores for pain were 4.89±2.12 (control) and 4.58±2.77 (test) points out of 10; for noise, these were 4.68±2.33 (control) and 4.55±2.55 (test), and for vibration, the values were 4.26±2.0 (control) and 4.18±2.48 (test). HR averages were 72.34±3.39 (control) and 75.97±9.78 (test) beats/min. No statistically significant differences were observed between the devices. Conclusion:The pain, discomfort levels, and scaling time of the new piezoelectric ultrasonic scaler did not differ from those of the conventional device. Further research and development are necessary for more prominent pain-relief effects of scaling devices.